Pengaruh Penerapan Virtual Lab Berbantuan LKPD Menggunakan Model Pembelajaran Kooperatif Tipe Group Investigation Terhadap Kompetensi Peserta Didik Kelas XI SMAN 5 Padang - Wahyu Kurnia; Hidayati Hidayati; Ramli Ramli (Universitas Negeri Padang, 2017)
Technological developments can be utilized in the manufacture of learning media that can increase the interest of learners to learn, make learners more active so as to enhance the competence of learners. One of the learning media that can increase the interest of learners is Virtual Laboratory LKPD Assisted Using Cooperative Learning Model of Group Investigation. The purpose of this research is to know the effect of Virtual Laboratory Supported by LKPD Using Cooperative Learning Model of Group Investigation Group on the competence of students of class XI SMAN 5 Padang. This tipe of research is Pre-Experimental Design with One Shot Case Study. Sampling is done by Purposive Sampling technique. From the data analysis for the three competencies obtained the following results: 1)The average score of knowledge competence of learners after using LKPD assisted virtual laboratory using cooperative learning model in practice activity is 84,09, 2) Use of LKPD assisted virtual laboratory using cooperative learning model type group investigation on knowledge competence with rvalue >rtable, percentage of influence 20,25%, and 3) the competence of the students’ skill has increased the general competence from the lab to the next practicum